PENGARUH SUMBER BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA - Muhamat Qahfi; Norhayatun Norhayatun; Merry Fitriaty (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
Sources of learning and independence of learning have an important effect on student learning outcomes because with the presence of learning resources in school and high learning independence can improve student learning outcomes. This study aims to determine the effect of partial and simultaneous learning resources and independence of learning on the students' economic subjects class XI MAN Sampit year 2016 / 2017.The approach in this study is ex-postfacto research with a population of 304 students. Sampling technique used is a proportional random sampling technique in which the sample amounted to 79 students.Tekhnik data analysis is done linear regression multiplier that has fulfilled the requirements analysis test. The results of this study indicate that there is a partially positive and simultaneous influence of the source and independence of learning on the learning outcomes of economic subjects of students of class XI MAN Sampit 2016/2017 academic year.